STATUS KESUBURAN TANAH DI TAMAN HUTAN HUJAN TROPIS INDONESIA (TH2TI) BANJARBARU KALIMANTAN SELATAN - Asmaul Zanah; Ahmad Yamani; Susilawati Susilawati (Jurnal Sylva Scienteae, 2026)
The purpose of this study was to identify and analyze the status of soil fertility levels in the Tropical Rainfall Park of Indonesia (TH2TI) Banjarbaru, South Kalimantan. Data from land units that became observation points, showed different land cover and area. Land unit 1 and land unit 3 with sengon land cover vegetation have an area of 0.49 ha and 0.43 ha respectively. Land unit 2 with jabon land cover vegetation has an area of 0.49 ha, and land unit 4 with mahogany land cover vegetation has an area of 1.00 ha. Soil fertility at the research site per land unit has a low level of soil fertility. The low soil fertility status at the research site is caused by low base saturation and the soil type which is dominated by yellow red podzolic soil, where this soil has relatively low fertility, then experiences leaching caused by high rainfall.